A karyotypic study on Silene, section Siphonomorpha species of Turkey - (:unkn) unknown (WILEY, 2008)
Karyology of the eight taxa of Silene sect. Siphonomorpha known from Turkey was investigated. Diploid chromosome numbers and the basic chromosome number of the studied taxa were obtained as 2n=24 and x=12, respectively. A karyotype analysis of the studied taxa was carried out and the chromosome numbers of S. splendens, S. amana and S. phrygia were determined for the first time. The smallest chromosomes were observed in S. fruticosa and the largest in S. italica subsp. italica. Silene splendens showed the highest A(1) index, whereas S. amana had the highest interchromosomal asymmetry coefficient (A(2)). The karyologic results of the study and the analysis of chromosomal morphology of each taxon is presented.
Keywords: EAST ANATOLIA; L. CARYOPHYLLACEAE; SOUTH ANATOLIA